Contour integration deficits at high spatial frequencies in children treated for anisometropic amblyopia - Jiang, Shu-Qi; Chen, Yan-Ru; Liu, Xiang-Yun; Zhang, Jun-Yun (Frontiers in Neuroscience, 2023)
Purpose This study was conducted to reexamine the question of whether children treated for anisometropic amblyopia have contour integration deficits. To do so, we used psychophysical methods that require global contour processing while minimizing the influence of low-level deficits: visibility, shape perception, and positional uncertainty. Methods Thirteen children with anisometropic amblyopia (age: 10.1 ± 1.8 years) and thirteen visually normal children (age: 10.8 ± 2.0 years) participated in this study. The stimuli were closed figures made up of Gabor patches either in noise or on a blank field. The contrast thresholds to detect a circular contour on a blank field, as well as the thresholds of aspect ratio and contour element number to discriminate a circular or elliptical contour in noise, were measured at Gabor spatial frequencies of 1.5, 3, and 6 cpd for amblyopic eyes (AEs), fellow eyes (FEs), and normal control eyes. Visual acuities and contrast sensitivity functions for AEs and FEs and the Randot stereoacuity were measured before testing. Results The AEs showed contrast deficits and degraded shape perception compared to the FEs at higher spatial frequencies (6 cpd). When the influence of abnormal contrast sensitivity and shape perception were minimized, the AEs showed contour integration deficits at spatial frequencies 3 and 6 cpd. These deficits were not related to basic losses in contrast sensitivity and acuity, stereoacuity, and visual crowding. Besides, no significant difference was found between the fellow eyes of the amblyopic children and the normal control eyes in the performance of contour integration. Conclusion After eliminating or compensating for the low-level deficits, children treated for anisometropic amblyopia still show contour integration deficits, primarily at higher spatial frequencies, which might reflect the deficits in global processing caused by amblyopia. Contour integration deficits are likely independent of spatial vision deficits. Refractive correction and/or occlusion therapies may not be sufficient to fully restore contour integration deficits, which indicates the need for the development of clinical treatments to recover these deficits.